Microplastics in soil: a comprehensive review of analytical techniques - Gündoğdu, Sedat; Akça, Muhittin Onur; Gursoy, Mehmet; Yılmaz, Murat; Zhang, Xiaoyu; Rodríguez-Seijo, Andrés; Bibi, Aisha; Di Gioia, Maria Luisa; Velimirovic, Milica (Frontiers in Soil Science, 2025)
Microplastics (MPs) pollution has increasingly been recognized as a critical environmental issue impacting terrestrial ecosystems, particularly soil matrices. This review comprehensively evaluates existing identification techniques for MPs in soil, highlighting the complexities associated with soil matrices, such as heterogeneity, organic matter content, and diverse particle sizes. Current methods, including sieving, filtration, density separation, chemical digestion, and spectroscopic analysis (e.g., FTIR, Raman spectroscopy), are critically assessed for efficiency, reliability, and applicability. Our analysis identifies significant methodological inconsistencies across studies, emphasizing the urgent need for standardized analytical protocols to enable reliable comparative assessments. Recommendations include the implementation of stringent quality assurance/quality control measures to mitigate cross-contamination and enhance data quality. Given the projected increase in global plastic production and consequent MPs pollution, it is imperative to develop standardized, scalable, and cost-effective methodologies for monitoring MPs in soil environments.